ANALISIS PERILAKU PATUH PAJAK ORANG PRIBADI BERDASARKAN THEORY OF PLANNED BEHAVIOR DAN KEPERCAYAAN TERHADAP PEMERINTAH - Sekti Ari, Dessanti Putri (FIA UB, 2019)
Tax compliance behavior is a real action taken by taxpayers to calculate, deposit, and report taxes. The level of tax compliance in Indonesia is still low. This is evidenced by the data from the OECD and the directorate general of tax performance reports. Therefore, the purpose of this study is to analyze the factors that influence individual tax compliance behavior by using Theory of Planned Behavior and trust in the government. The variables used in this study are attitudes, subjective norms, control of perceived behavior, trust in the government, tax compliance intention, and tax compliance behavior. Data were collected through online survey methods. The population of this study is individual taxpayers on theÂ Java island. The sampling method in this study is judgment sampling. This study used 120 respondents. The statistical method used in this research is Warp Partial Least Square (WarpPLS). The results of this study indicate that attitudes and subjective norms have a positive effect on the tax compliance intention and the tax compliance intention has a positive effect on tax compliance behavior. While perceived behavioral control does not have a positive effect on tax compliance intention, perceived behavioral control and trust in the government have no effect on tax compliance behavior.Â